2001
DOI: 10.1042/bj3560361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of histatin 5 and derived peptides on Candida albicans

Abstract: Three anti-microbial peptides were compared with respect to their killing activity against Candida albicans and their ability to disturb its cellular and internal membranes. Histatin 5 is an anti-fungal peptide occurring naturally in human saliva, while dhvar4 and dhvar5 are variants of its active domain, with increased anti-microbial activity. dhvar4has increased amphipathicity compared with histatin 5, whereas dhvar5has amphipathicity comparable with that of histatin 5. All three peptides caused depolarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 0 publications
3
69
0
1
Order By: Relevance
“…Substitution of functionally nonessential residues of Hst 5 with proline to disrupt any secondary structure resulted in unaltered candidacidal activity (10), showing that the degree of the amphipathic molecular moment is not involved in its fungicidal activity. Furthermore, synthetic variants of Hst 5 with increased (dhvar4) and decreased (dhvar5) amphipathic features both killed C. albicans (11). Comparison with amphipathic peptides that translocated across and disrupted liposome membranes showed that Hst 5 did not interact with model membranes (12).…”
mentioning
confidence: 99%
“…Substitution of functionally nonessential residues of Hst 5 with proline to disrupt any secondary structure resulted in unaltered candidacidal activity (10), showing that the degree of the amphipathic molecular moment is not involved in its fungicidal activity. Furthermore, synthetic variants of Hst 5 with increased (dhvar4) and decreased (dhvar5) amphipathic features both killed C. albicans (11). Comparison with amphipathic peptides that translocated across and disrupted liposome membranes showed that Hst 5 did not interact with model membranes (12).…”
mentioning
confidence: 99%
“…Structural analysis has revealed that histatins differ from amphipathic membrane-active peptides by virtue of their reluctance to rapidly adopt helical structures in moderately hydrophobic environments and the weak amphipathicity of their ␣-helical structures (8,9). The interaction of histatin 5 with liposome vesicles, mitochondria, or C. albicans blastoconidia does not result in a massive disintegration and depolarization of the membranes such as is achieved with strongly amphipathic peptides (9)(10)(11). The general consensus therefore is that the ultimate events in histatin-provoked cell death are not restricted to direct membrane effects.…”
mentioning
confidence: 99%
“…Their effects on cytoplasmatic membranes are limited and permeabilization of the microbial membrane is a secondary effect rather than the primary cause of their antimicrobial activity (Ruissen et al 2001(Ruissen et al , 2002Den 20 Hertog et al 2005, Welling et al 2007. The most potent anti-Candida member of this family is Hst 5 and analysis of its sequence showed the presence of lysine and arginine residues (Helmerhorst et al 1997).…”
Section: Antifungal Effect Of Homopeptides On Sessile C Albicans Cellsmentioning
confidence: 99%